2022
DOI: 10.3389/fphar.2022.795530
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Earthworm: Speciation and Bioaccessibility of Arsenic and Its Potential Health Risks

Abstract: Arsenic in environmental health has caused public concerns all over the world. However, high levels of arsenic residues in medicinal animals have not received enough attention. Medicinal earthworms are consumed widely in China, but its arsenic potential health risks to humans are unknown. This work investigated the total concentration, bioaccessibility, and speciation of arsenic in earthworms by ICP-MS and HPLC-ICP-MS to evaluate its potential health risks to humans. Arsenic was found in all earthworms at conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the assay of wormcasts, it was found that the ARG concentration in the treatment group under high arsenic stress was generally lower than that in the treatment group with low arsenic addition. Studies have shown that arsenic has a toxic effect on earthworms [ 49 ], the severity of which increases with increasing arsenic concentration, thus reducing their transformation metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In the assay of wormcasts, it was found that the ARG concentration in the treatment group under high arsenic stress was generally lower than that in the treatment group with low arsenic addition. Studies have shown that arsenic has a toxic effect on earthworms [ 49 ], the severity of which increases with increasing arsenic concentration, thus reducing their transformation metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Medicinal earthworms are consumed widely in China, but the potential health risks from As are unknown. Li et al 63 have reported on work to investigate the total concentration, bioaccessibility, and speciation of As in earthworms by ICP-MS and HPLC-ICP-MS in order to evaluate the potential health risks to humans. Arsenic was found in all earthworms at concentrations ranging from 0.4 to 53.6 mg kg −1 .…”
Section: Arsenicmentioning
confidence: 99%
“…It is recognized that the use of phosphate-based fertilisers in agriculture in New Zealand can result in a modest increase in accumulated cadmium levels. Arsenic has been found in all earthworm species studied at concentrations ranging from 0.4 to 53.6 mg•kg −1 DW [79]. Arsenic, in regard to ecological safety, has become a worldwide public concern, as human exposure to arsenic is mostly through water and food [79].…”
Section: Non-essential Minerals-heavy Metalsmentioning
confidence: 99%
“…Arsenic has been found in all earthworm species studied at concentrations ranging from 0.4 to 53.6 mg•kg −1 DW [79]. Arsenic, in regard to ecological safety, has become a worldwide public concern, as human exposure to arsenic is mostly through water and food [79]. As the source of accumulation of arsenic is through the soil, it is challenging to control the accumulation of heavy metals such as arsenic in wild-harvested earthworms.…”
Section: Non-essential Minerals-heavy Metalsmentioning
confidence: 99%